Boundary conditions for a capillary fluid in contact with a wall - Gouin, H.; Kosiński, W. (Archives of Mechanics, 1998)
Contact of a fluid with a solid or an elastic wall is investigated. The wall exerts "molecular forces" on the fluid which is locally strongly non-homogeneous. The problem is approached with a fluid energy of the second gradient form and a wall surface energy depending on the value of the fluid density in the contact. From the virtual work principle and taking into account the fluid density, its derivative normal to the wall and the curvature of the surface, limit conditions are obtained.